2013
DOI: 10.4274/tod.25238
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporozda Depresyon ve Yaşam Kalitesine Etkisi

Abstract: Objective: The aim of this study was to identify risk factors for the development of depression in patients with osteoporosis, and to measure the psychosocial effects to the change in quality of life. Material and Methods: 125 patients with osteoporosis were included in the study. A questionnaire was completed which was including age, sex, marital status, education level, occupation, height, weight, alcohol use, smoking, physical activity level, milk consumption, previous fragility fracture of the patients. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…Fatigue, one of its most common symptoms, also contributes to inadequate employment and early retirement. Studies have also reported that most MS patients do not work 35,36. Similarly, in this study, most of the patients' lives changed because of MS.…”
Section: Discussionsupporting
confidence: 73%
“…Fatigue, one of its most common symptoms, also contributes to inadequate employment and early retirement. Studies have also reported that most MS patients do not work 35,36. Similarly, in this study, most of the patients' lives changed because of MS.…”
Section: Discussionsupporting
confidence: 73%